A Mixture of Water-Soluble Polysaccharides Reduces Caspase-1 and IL-1β Inflammatory Responses by Cutibacterium acnes in vitro in Reconstructed Human Epidermis (RHE) - Gruber JV; Terpak N; Massard S; Chen X; Kim Y (Dove Medical Press, 2024)
James V Gruber,1 Nicole Terpak,2 Sebastien Massard,2 Xiang Chen,2 Yurah Kim2 1Research, Vantage, Fairfield, NJ, USA; 2Research, Vantage, Warren, NJ, USACorrespondence: James V Gruber, Email vincent.gruber@vantagegrp.comIntroduction: It is well established that Cutibacterium acnes (C. acnes) is a common skin commensal microorganism that has been linked to acne. In acne flare-ups, C. acnes can be found in abundant levels within the inflammatory lesions (called comedones) associated with the skin disease. Recently, it was reported that 3D reconstructed human epidermis (RHE) treated with viable cultures of C. acnes can elicit β-defensin antimicrobial peptide responses in the skin and can weaken the skin barrier of the RHE after three days of exposure to C. acnes.Methods: Employing a modification of this in vitro assay, RHE was pretreated with C. acnes for 48 hours, then further treated with a mixture of water-soluble polysaccharides (STRATAPHIX™ POLY, "Polysaccharide Blend") previously shown to reduce inflammasome-mediated inflammatory responses in normal human epidermal keratinocytes (NHEK). Two inflammasome-mediated inflammation markers were tested, including caspase-1, a potent protease enzyme activated by NOD-like receptor protein (NLRP)-induced inflammasome activation, and interleukin-1β (IL-1β), a cytokine which is activated from inactive pro-IL-1β by caspase-1.Results: The treatment of the RHE tissues with C. acnes for 48 hours elicited an inflammatory response measured with both markers compared against untreated tissues. Treatment of the tissues with 1% and 2% salicylic acid for 24 hours after C. acnes treatment increased the inflammatory response measured with both markers. Application of the water-soluble polysaccharides in combination with 1% and 2% of salicylic acid significantly reduces expression of both active caspase-1 and IL-1β compared against the tissues treated with C. acnes and salicylic acid alone.Discussion: The results lend further support to previously reported work which was done on NHEKs treated with ultraviolet B (UVB) light and adenosine triphosphate (ATP) and demonstrate that the same mixture of polysaccharides can have a modulating effect against bacterial and chemical induced inflammation in RHE.Keywords: Cutibacterium acnes, In vitro, tissues, inflammation, caspase-1, IL-1β, topical